Moving target defence in 6G UAV networks - Alismail, Ahmed; Whitworth, Huw; Al-Rubaye, Saba; Tsourdos, Antonios; James, Liz; Baker, Lawrence (Institute of Electrical and Electronics Engineers (IEEE), 2024)
This paper focuses on enhancing the resilience of Unmanned Aerial Vehicle (UAV) networks against reconnaissance cyber-attacks. We introduce a novel algorithmic framework for IP and Port hopping, specifically tailored for UAV networks, to implement Moving Target Defense (MTD). The algorithm dynamically changes IP addresses and communication ports, increasing network unpredictability and thwarting reconnaissance attempts. Furthermore, we combine Network-based Moving Target Defense with sixth generation (6G) Software-Defined Networking (SDN) to enable real-time reconfiguration of network policies, providing proactive defense capabilities. Additionally, we integrate honeypots as a cyber deception strategy to divert potential attackers and gather valuable insights into their tactics. Extensive simulations demonstrate the effectiveness of our approach in reducing reconnaissance success rates and enhancing UAV network security.
Keywords: 46 Information and Computing Sciences; 4604 Cybersecurity and Privacy